2016
DOI: 10.2166/wh.2016.204
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood diversity of potentially pathogenic bacteria in drinking water from the city of Maroua, Cameroon

Abstract: This study examined the spatial variation of potential gastrointestinal pathogens within drinking water sources and home storage containers in four neighborhoods in Maroua, Cameroon. Samples were collected from source (n = 28) and home containers (n = 60) in each study neighborhood. Pathogen contamination was assessed using quantitative polymerase chain reaction, targeting Campylobacter spp., Shiga toxin producing Escherichia coli (virulence genes, stx1 and stx2), and Salmonella spp. Microbial source tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…In addition to quantifying coliform concentrations, we quantified the concentrations of four enteric pathogens in the household drinking water and fecal samples using a QX200 droplet digital PCR (ddPCR) system (Bio‐Rad, Hercules, California). The enteric pathogens, which included Arcobacter spp., Campylobacter (targeting 16S rRNA gene of C. jejuni , C. coli , and C. lari ), Salmonella spp., and enterohemorragic E. coli (targeting virulence genes stx1 and stx2 ) were selected based on their probability of being present in stored drinking water samples in a LMIC setting (Healy‐Profitós et al, ). EvaGreen ddPCR analysis was used to quantify Arcobacter, Campylobacter , and Salmonella , (Healy‐Profitós et al, ; Klase et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to quantifying coliform concentrations, we quantified the concentrations of four enteric pathogens in the household drinking water and fecal samples using a QX200 droplet digital PCR (ddPCR) system (Bio‐Rad, Hercules, California). The enteric pathogens, which included Arcobacter spp., Campylobacter (targeting 16S rRNA gene of C. jejuni , C. coli , and C. lari ), Salmonella spp., and enterohemorragic E. coli (targeting virulence genes stx1 and stx2 ) were selected based on their probability of being present in stored drinking water samples in a LMIC setting (Healy‐Profitós et al, ). EvaGreen ddPCR analysis was used to quantify Arcobacter, Campylobacter , and Salmonella , (Healy‐Profitós et al, ; Klase et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The enteric pathogens, which included Arcobacter spp., Campylobacter (targeting 16S rRNA gene of C. jejuni , C. coli , and C. lari ), Salmonella spp., and enterohemorragic E. coli (targeting virulence genes stx1 and stx2 ) were selected based on their probability of being present in stored drinking water samples in a LMIC setting (Healy‐Profitós et al, ). EvaGreen ddPCR analysis was used to quantify Arcobacter, Campylobacter , and Salmonella , (Healy‐Profitós et al, ; Klase et al, ). For enterohemorrhagic E. coli ( stx1 and stx2 ), a probe‐based ddPCR analysis was performed (Healy‐Profitós et al, ; Klase et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water is stored in various containers which include jerry cans, buckets, drums, basins and local pots [11][12][13]. It has been reported that when collection of water from sources of high quality is possible, contamination during transport, handling and storage and poor hygienic practices often results and can cause poor health outcomes [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%